To a God Unknown play still
To a God Unknown play still. This scene shows Joseph Wayne and Elizabeth just before she slips and falls.This production was directed by Kay Bosse and performed at the Blair Hall Theater, Sinclair Community College, Dayton, Ohio. The actors are unknown.